Nutritional characteristics and phenolic compounds of ripe fruit pulp from six accessions of Mammea americana L. - Armelle Péroumal; Audrey Vingadassalon; Genica Lawrence; Sandra Adenet; Katia Rochefortd; Louis Fahrasmane; Guylène S Aurore (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2022)
Mamey apple (Mammea americana) is a tropical fruit largely consumed and more and more coveted as it is a rich source of antioxidants. There is considerable interest in fruits phenolic compounds due to their different characteristics and particularly to their role in protection against cardiovascular diseases and cancers through their antioxidant activity. Nutritional characteristics were determined in six mamey apple fruit accessions: Sonson, Pavé 11, Lézarde, Ti Jacques, Escouët and Antonio. The pulps of the ripe fruits were analyzed for moisture, ash, total lipid, total protein, and carbohydrate contents.  This study represents a detailed report of phenolic compounds in mamey apple pulp. The metabolite profiling associated with the antioxidant potential represents an important step to the bioactive molecules characterization. The results showed that the accessions studied contained three main classes of phenolic compounds: flavan-3-ols, phenolic acids and flavonols. Those phenolic compounds characterization was then carried out first using liquid chromatography (HPLC) coupled to Diode Array Detector (DAD). Finally, spectral characteristics and fragmentations were acquired by Mass Spectrometry (MS) using the Electrospray Ionization Interface (ESI). All the identified compounds are interesting metabolites known for their biological properties and nutritional benefits